Flap Reconstruction of the Oropharyngeal Defect After Tumor Resection via Combined Transcervical and Transoral Approach in Patients With HPV-Positive and -Negative Oropharyngeal Squamous Cell Carcinoma - Chen, Jiaming; Fang, Jugao; Zhong, Qi; Feng, Ling; He, Shizhi; Ma, Hongzhi; Hou, Lizhen; Lian, Meng; Wang, Ru; Shen, Xixi; Yang, Yifan (Frontiers in Oncology, 2022)
Objective： To investigate a novel surgical approach of combined transcervical parapharyngeal space(PPS) with the transoral approach to dissect oropharyngeal cancer. Methods: 31 patients who were pathologically diagnosed with oropharyngeal cancer and had undergone surgical treatment in Beijing Tongren Hospital during 2018.06 and 2020.12 were enrolled. All patients were squamous cell carcinoma. There were 25 males and 6 females, the age ranged between 44 to 70 years old. The number of patients with T1, T2, T3, and T4 stage disease was 8,15,8and 0, respectively, according to the American Joint Committee on Cancer staging method, 8th edition. After the dissection of the submandibular and cervical lymph nodes, the parapharyngeal space was exposed, and the parapharyngeal space lymph node and the outer borderline of the tumor were dissected, and then, dissect the inner borderline of the tumor via transoral approach, the tumor was dissected en bloc, the defects were reconstructed with the flap from the neck through the parapharyngeal space. Results： Among the patients enrolled, 21 were HPV positive and 10 were HPV negative. 8 patients were free of lymph node metastasis. The tumor resection margins were negative in all 31 patients. Safe and sufficient excision of tumors was feasible by this new surgical approach avoiding complications associated with mandibulotomy or lip-splitting. All patients had no obvious dysfunctions of swallowing and voice. By the time of this follow-up, none died caused by OPSCC, and only two patients suffered from local recurrence. The 3-year survival rate is 100%, and the 3-year recurrence-free survival rate is 84.58%. Conclusion: The surgical approach of Combined transcervical parapharyngeal space with the transoral approach was effective and safe. On this basis, this approach has the advantage of fewer postoperative complications and better functional results.